Perluasan Makna Final Pada Putusan Pengadilan Tata Usaha Negara - Sihombing, Eka NAM; Cynthia Hadita (Talenta Publisher, Universitas Sumatera Utara, 2024)
The decision of the Administrative Court is one of 'final' nature, there is an expansion of meaning to refer to the legal status of the decision. Once a final decision has been issued by the Administrative Court, the parties to the dispute can no longer appeal or make other legal efforts to challenge or change the decision, except in certain circumstances regulated by law. The term 'final' indicates that the decision is irreversible and legally binding for all parties involved in the case. However, the definition of 'final' in a particular situation may vary depending on the applicable laws in the country. The purpose of this research is to examine the expansion of the meaning of final in Administrative Court Decisions usually related to the annulment, amendment, or confirmation of Administrative Court decisions that have become the subject of disputes. This research uses normative juridical legal research methods. In this article, researchers have concluded that the expansion of the meaning of 'final' in the context of State Administrative Court (PTUN) decisions refers to the legal status of the decision. The term 'final' indicates that the decision is irreversible and becomes a legally binding decision for the parties involved in the case. In practice, final PTUN decisions have the same legal force as other court decisions and must be obeyed by the parties involved in the case. This is important to maintain legal certainty and the integrity of the state administrative justice system.